(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the field of French grammar, French prepositional pronouns have been an important basis for VGGak’s research. A distinctive feature of the system of prepositional pronouns in French is the presence of double forms: independent and prepositional pronouns. VGGak in his scientific works came to the conclusion that the functioning and development of subjective prepositional pronouns is primarily determined by the needs of syntax, not morphology. The syntactic connection of the personal verb with the object is necessary to express the relationship of the action with its carrier. The personal form of the verb in French has lost this ability, and the verb endings are simply the conjugation form, indicating the persons of speech. VGGak believed that the functions of prepositional pronouns are a special type of auxiliary subjects, and il parle compounds are two-part sentences. At the same time, the deviation of pronouns from their main function - taking the place of the missing member of the sentence - indicates its lexicalization or morphologicalization.